DESIGN AND RESEARCH OF MATHEMATICAL MODEL FOR INFORMATION SECURITY SYSTEM IN COMPUTER NETWORK - Корнієнко, Б.Я.; Галата, Л.П. (Science-based technologies, 2017)
This article presents simulation modeling process as the way to study the behavior of the Information Security system. Graphical Network Simulator is used for modeling such system and Kali Linux is used for penetration testing and security audit. The main approaches to simulation of computer networks are considered. The functional capabilities of the GNS3 package are explored. When building an imitation model, the main components of information protection were used. The Kali Linux package implements a number of attacks. Using simulation in the design of computer systems done the following: estimated bandwidth network and its components identified bottlenecks in the structure of computer systems; compared different options for computer systems; made a promising forecast for the development of computer systems; provides future requirements for bandwidth.